TECHNOLOGICAL ADVANCEMENT IN AGRICULTURE AND THE IMPACT ON ENVIRONMENT - et. al., Dr. Megha virmani Arya (International Journal of Modern Agriculture, 2021)
Agriculture is among the most significant sector in India and is important for the maintenance and the growth of India’s economy. Around 70% of the household & 10% of urban-population is reliant on on Agriculture as the source of livelihood. Today, India is the largest producer of various agriculture products like coffee, tea, rice, oil meals, spices, meat, fresh fruits and fresh vegetable and its preparation & marine-product to an international market. The Agriculture Research System in India is a height of the process that was started in 19th century & resulted in establishment of ICAR (Indian Council of Agricultural Research) on the suggestion of a Royal-Commission-On-Agriculture in the year 1929. In the current research system, Indian-Council-of-Agriculture-Research (ICAR) at the National-level mainly help, promote & collaborate research & Education in India. Advancement in technology is the basic to coming future of farming because farmer struggle to feed world with partial natural-resource. The agri-tech solution helps to provide backbone to all over growth of Sustainable-Agriculturing & food-production. The investment is focused at agri-tech startup & disruptive market-newcomer. New technology, resources input & economic-incentive that leads to increase in agricultural production. The future technology development for food-production & handling system should be non-polluting, should reduce environmental & health-hazards & not inspire new-regulatory restriction.